Documenting Interspecific Predation in Odonata: Observations of Ischnura Senegalensis Preying on Agriocnemis Pygmaea in Rice Fields of Faculty of Agriculture, Rajarata University of Sri Lanka, Puliyankulama, Anuradhapura District - Harsha, Piumal (Journal of Wildlife, 2024)
Interspecific predation within Odonata is a critical yet underexplored aspect of their ecological interactions. This short communication reports a novel observation of Ischnura senegalensis preying upon Agriocnemis pygmaea in rice fields at the Faculty of Agriculture, Rajarata University of Sri Lanka. Documented on March 22, 2024, during the reproductive stage of the rice field, the predatory event involved a female I. senegalensis feeding on the head of a female A. pygmaea. Predation, characterized by the use of mandibles and lasting at least 15 minutes, reveals significant predatory efficiency and behavioral specialization. This observation fills a gap in the understanding of I. senegalensis feeding behavior in Sri Lanka and contributes to the broader knowledge of Odonate predator-prey dynamics. The findings highlight the importance of these interactions in maintaining ecological balance and suggest further research into the impacts of such predatory behaviors on agricultural ecosystems.
Keywords: Agriocnemis pygmaea; Anuradhapura; Interspecific Predation; Ischnura senegalensis; Rice Fields